Self-error-rejecting quantum state transmission of entangled photons for faithful quantum communication without calibrated reference frames. (30th October 2019) - Guo, Peng-Liang; Li, Tao; Ai, Qing; Deng, Fu-Guo
Abstract: We propose an alignment-free two-party polarization-entanglement transmission scheme for entangled photons by using only linear-optical elements, requiring neither ancillary photons nor calibrated reference frames. The scheme is robust against both the random channel noise and the instability of reference frames. Furthermore, the success probabilities for entanglement transmission are, in principle, improved to unity when active polarization controllers are used. The distinct characters of a simple structure, being easy to implement, and the high fidelity and efficiency make our protocol very useful for long-distance quantum communications and distributed quantum networks in practical applications. As an example, we give its application in a reference-frame-alignment-free quantum key distribution protocol with entanglement.